2001
DOI: 10.1152/physiolgenomics.00061.2001
|View full text |Cite
|
Sign up to set email alerts
|

Gene induction and categorical reprogramming during in vitro human endometrial fibroblast decidualization

Abstract: Gene induction and categorical reprogramming during in vitro human endometrial fibroblast decidualization. Physiol Genomics 7: 135-148, 2001. First published September 21, 2001; 10.1152/physiolgenomics.00061.2001.-Human decidual fibroblasts undergo a differentiative commitment to the acquisition of endocrine, metabolic, and structural cell functions in a process known as decidualization. Decidualization is critical for embryo implantation and placental function. We characterized gene expression pattern kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 40 publications
11
102
0
1
Order By: Relevance
“…Although most of the novel gene products that were observed to be affected in the present study were already known to be involved in endometrial functionality from previous studies (see Table 7 for details), we are reporting for the first time that these were differentially regulated by high-affinity antiprogestin resulting in implantation failure in the rhesus monkey. Additionally, the observation in the present study that while a cohort of gene expression was consistent between days 4 and 6 after ovulation in a fecund cycle, a group of genes showed specific repression and derepression in the time course makes us to assume that endometrial receptivity in the rhesus monkey is associated with categorical reprogramming in endometrial tanscriptomics as observed in human endometrial fibroblasts in vitro (Brar et al 2001), human placental villous cytotrophoblasts in vitro , and mouse decidual cells (Kashiwagi et al 2007). We believe that elucidation of the time course pattern of endometrial receptivity associated transcriptomic networks will be beneficial to clinical sciences in improvising strategies to assist the establishment of pregnancy.…”
Section: Implantation-stage Endometrial Transcript Profilessupporting
confidence: 57%
“…Although most of the novel gene products that were observed to be affected in the present study were already known to be involved in endometrial functionality from previous studies (see Table 7 for details), we are reporting for the first time that these were differentially regulated by high-affinity antiprogestin resulting in implantation failure in the rhesus monkey. Additionally, the observation in the present study that while a cohort of gene expression was consistent between days 4 and 6 after ovulation in a fecund cycle, a group of genes showed specific repression and derepression in the time course makes us to assume that endometrial receptivity in the rhesus monkey is associated with categorical reprogramming in endometrial tanscriptomics as observed in human endometrial fibroblasts in vitro (Brar et al 2001), human placental villous cytotrophoblasts in vitro , and mouse decidual cells (Kashiwagi et al 2007). We believe that elucidation of the time course pattern of endometrial receptivity associated transcriptomic networks will be beneficial to clinical sciences in improvising strategies to assist the establishment of pregnancy.…”
Section: Implantation-stage Endometrial Transcript Profilessupporting
confidence: 57%
“…During this time, numerous genes are regulated in a time-dependent manner as previously shown by others (Brar et al, 2001;Tierney et al, 2003). In order to elucidate the role of HOXA10 during decidualization, HOXA10 was first silenced in HESCs using siRNA and subsequently treated with H + cAMP for 48 h. This technique efficiently knocked down HOXA10 mRNA and protein expression (Fig.…”
Section: Identification Of Hoxa10 Target Genes In Decidualizing Hescsmentioning
confidence: 67%
“…Other microarray studies have identified the genes that are most prominently regulated during decidualization and have provided insight to types of transformations that occur (Brar et al, 2001;Tierney et al, 2003;Takano et al, 2007). While identification of a function for a particular gene during this process in human cells has been a challenge, techniques involving gene silencing in combination with microarray analysis with the use of bioinformatics tools have made it feasible to define a role for a particular gene of interest during decidualization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LEFTYA and LEFTYB were demonstrated by microarray analysis and verified by northern blot to be one of the most abundantly induced factors in the decidua that supports implantation (Brar et al 2001). Moreover, expression of the LEFTY processing enzyme SPC5/6 was significantly increased within HESC during decidualization in vitro (Okada et al 2005).…”
Section: Humanmentioning
confidence: 85%